2017
DOI: 10.2147/dmso.s117982
|View full text |Cite
|
Sign up to set email alerts
|

Emerging use of combination therapies for the management of type 2 diabetes – focus on saxagliptin and dapagliflozin

Abstract: AimsThe aim of this article is to review the safety and efficacy data of dapagliflozin, saxagliptin, and their combination in the management of patients with type 2 diabetes. Evidence for the use of the single-tablet combination formulation is also presented.MethodsA nonsystematic literature review was performed using the Ovid, PubMed, and Google Scholar databases.ResultsThe addition of dapagliflozin/saxagliptin to metformin can lower mean hemoglobin A1c by as much as 1.47% and lead to weight loss of 0.5–2.0 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
(329 reference statements)
0
12
0
Order By: Relevance
“…In the experimental animal studies, SGLT2 showed anti-atherosclerotic effects through anti-oxidant effects 6) . Further, SGLT2 and DPP4 showed synergic effects on the anti-atherosclerotic effect in the experimental study 16,17) , and the preliminary clinical study [18][19][20] . Intestinal sodium glucose cotransporter-1 inhibition was reported to enhance glucagon-like peptide-1 (GLP-1) secretion in normal and diabetic rodents 21) .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the experimental animal studies, SGLT2 showed anti-atherosclerotic effects through anti-oxidant effects 6) . Further, SGLT2 and DPP4 showed synergic effects on the anti-atherosclerotic effect in the experimental study 16,17) , and the preliminary clinical study [18][19][20] . Intestinal sodium glucose cotransporter-1 inhibition was reported to enhance glucagon-like peptide-1 (GLP-1) secretion in normal and diabetic rodents 21) .…”
Section: Discussionmentioning
confidence: 86%
“…In the real world, SGLT2 is frequently added to DM patients similar to this study 20) . And preliminary clinical study showed that the combination therapies of DPP4 and SGLT2 seem to be effective in the treatment of patients with type 2 DM 19,20) . These findings are similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The function of DPP‐4is with sulphonylurea mechanistically relies on residual β‐cell activity, while SGLT‐2is work complementarily to DPP4is, reducing hyperglycaemia through renal excretion of glucose, independent of insulin secretion, thus reducing glucotoxicity and β‐cell burden. The risk of genital infections with combination therapy is lower than that observed with DAPA alone, which is suggestive of a protective effect …”
Section: Discussionmentioning
confidence: 89%
“…Studies have reported that the sodium‐glucose cotransporter‐2 inhibitor (SGLT‐2i) dapagliflozin (DAPA) plus the dipeptidyl peptidase‐4 inhibitor (DPP‐4i) saxagliptin (SAXA) in combination with metformin provides superior HbA1c reductions versus either agent added to metformin alone, with a lower risk of hypoglycaemia and BW gain . The risk of genital infection is lower in treatment regimens with the combination of DAPA + SAXA than DAPA monotherapy . However, validation is needed to determine the long‐term efficacy of DAPA + SAXA versus injectable insulin as an add‐on to metformin therapy in patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…[1112] Improvement in glycaemic control with combination of saxagliptin and metformin is established for better tolerance without the incidence of weight gain. [1314] Moreover, this combination poses improvement in quality-adjusted life-years (QALYs) apart from its effectiveness and cost-effectiveness. [151617]…”
Section: Introductionmentioning
confidence: 99%